Analysis and numerical simulation of a parabolic equation with non-local terms - Límaco, Juan Pablo (2025)
In this work, we investigate the existence and uniqueness of global strong solutions, as well as the exponential decay of these solutions in bounded domains, for an initial-boundary value problem associated with parabolic equations involving nonlocal terms. The theoretical results are complemented by numerical simulations obtained using the finite element method for the spatial variable and the finite difference method for the temporal variable.